Analysis of Air Gap Magnetic Field and Torque of the Slotted-type Magnetic Couplers - Yang Chaojun; Ding Yifei; Tai Jiangxi; Zhu Jiwei; Hang Tian; Yang Fan (Jixie chuandong)
In order to solve the problem of calculating the air gap magnetic field and torque of slotted-type magnetic couplers, a subdomain analysis model is introduced. The magnetic couplers are divided into five regions along the axis, the boundary equations are established at the interfaces of each region. According to the alternating arrangement characteristics of yoke teeth and the conductor and the vector magnetic potential formulas in yoke teeth and the copper conductor disk are deduced respectively. Due to the end effect, Schwarz-Christoffel mapping is used to modify the coefficient of the flux density at the end face of the cogging. On the basis of obtaining the vector magnetic potential of the yoke iron and conductor respectively, the formulas of the air gap magnetic field and electromagnetic torque are deduced. The structure parameters of the slotted-type magnetic couplers are substituted into the theoretical model to calculate the axial air-gap magnetic field distribution and mechanical characteristic curves. By comparing the results with those obtained by finite element simulation, the accuracy of the theoretical model is verified and the cause of the error is analyzed.